2021
DOI: 10.1101/2021.12.22.473926
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intramolecular interactions enhance the potency of gallinamide A analogs againstTrypanosoma cruzi

Abstract: Gallinamide A, a metabolite of the marine cyanobacterium Schizothrix sp., selectively inhibits cathepsin L-like cysteine proteases. We evaluated potency of gallinamide A and 23 synthetic analogs against intracellular Trypanosoma cruzi amastigotes and the cysteine protease, cruzain. We determined the co-crystal structures of cruzain with gallinamide A and two synthetic analogs at ~2Å. SAR data revealed that the N-terminal end of gallinamide A is loosely bound and weakly contributes in drug-target interactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In this instance, one of the compounds was shown to have a LD 50 of 5.1 ± 1.4 nM, while compound 90 had a LD 50 of 14.7 nM against Trypanosoma cruzi . Following this, Silva et al found compounds 92 , 93 and 94 , whose activities exceeded 90 by 15 times [ 74 ]. The structural difference between 92 and 93, in comparison with 94, was the lack of CH 2 -CH 2 -Ph in P1, which excludes the stabilizer effect of intramolecular interactions between indole and CH 2 -CH 2 -Ph.…”
Section: Covalent Inhibitors For Neglected Diseasesmentioning
confidence: 97%
See 4 more Smart Citations
“…In this instance, one of the compounds was shown to have a LD 50 of 5.1 ± 1.4 nM, while compound 90 had a LD 50 of 14.7 nM against Trypanosoma cruzi . Following this, Silva et al found compounds 92 , 93 and 94 , whose activities exceeded 90 by 15 times [ 74 ]. The structural difference between 92 and 93, in comparison with 94, was the lack of CH 2 -CH 2 -Ph in P1, which excludes the stabilizer effect of intramolecular interactions between indole and CH 2 -CH 2 -Ph.…”
Section: Covalent Inhibitors For Neglected Diseasesmentioning
confidence: 97%
“…Similarly to [ 73 ], Silva et al approached the CZ inhibitory potential of these compounds [ 74 ]. As a result, they explored P4 to module pharmacokinetics properties.…”
Section: Covalent Inhibitors For Neglected Diseasesmentioning
confidence: 99%
See 3 more Smart Citations